The Constitutionally-Bounded Legal Pluralism: Reconciling Inheritance Law and Women's Rights in Indonesia - Jinoto, Devin Irwan (Jurnal Cakrawala Hukum, 2025)
Indonesia's pluralistic legal order sustains a structural contradiction between positive inheritance law and customary (adat) traditions that systematically denies women their constitutionally guaranteed equal inheritance rights. Although the KUHPerdata establishes bilateral succession irrespective of sex, and the Kompilasi Hukum Islam provides enforceable inheritance entitlements for Muslim women, patrilineal customary systems operative among the Batak Toba, Sahu Tribe, Dayak, and Balinese Hindu communities exclude women from inheriting productive assets, particularly land, in direct contravention of Articles 27(1), 28D(1), and 28H(2) of the UUD 1945. Employing a normative legal research methodology through statutory, conceptual, and comparative approaches, this study analyzes primary legal materials including the UUD 1945, KUHPerdata, KHI, and Supreme Court jurisprudence, alongside secondary academic literature. The findings establish that the contradiction constitutes a failure of constitutional enforcement rather than a legitimate exercise of legal pluralism: Article 18B(2)'s recognition of customary rights is conditioned on non-contradiction with national law, a condition that gender-discriminatory inheritance norms demonstrably fail to satisfy. Reconciliation requires a five-pillar framework: legislative affirmation of constitutional supremacy over incompatible customary norms; binding Supreme Court jurisprudential guidance; constitutionally-bounded legal pluralism through institutionalized customary governance bodies; community legal education and women's empowerment; and a comprehensive national inheritance statute establishing a universal gender-equality floor across all inheritance systems.